Utilization of Biomasses from Landscape Conservation Growths Dominated by Common Ragwort (Jacobaea vulgaris Gaertn.) for Biomethanization - Jürgen Müller; Denny Wiedow; Mohammad Said Chmit; Till Beuerle (Plants, 2022)
The highly toxic species common ragwort (Jacobaea vulgaris Gaertn.) prefers to migrate into protected dry grassland biotopes and limits the use of the resulting biomass as animal feed. There is an urgent need for a safe alternative use of the contaminated biomass apart from landfill disposal. We investigated the optional utilization of biomethanization of fresh and ensiled common ragwort biomasses and evaluated their energetic potentials by estimation models based on biochemical characteristics and by standardized batch experiments. The fresh and ensiled substrates yielded 174 LN∙kg−1 oDM methane and 185 LN∙kg−1 oDM, respectively. Ensiling reduced the toxic pyrrolizidine alkaloid content by 76.6%; a subsequent wet fermentation for an additional reduction is recommended. In comparison with other biomasses from landscape cultivation, ragwort biomass can be ensiled readily but has a limited energy potential if harvested at its peak flowering stage. Considering these properties and limitations, the energetic utilization is a promising option for a sustainable handling of Senecio-contaminated biomasses in landscape conservation practice and represents a safe alternative for reducing pyrrolizidine alkaloid entry into the agri-food sector.